The Stability of a General Sextic Functional Equation by Fixed Point Theory. (24th December 2020) - Roh, Jaiok; Lee, Yang-Hi; Jung, Soon-Mo
Abstract : In this paper, we will consider the generalized sextic functional equation ∑ i = 0 7   7 C i − 1 7 − i f x + i y = 0 . And by applying the fixed point theorem in the sense of Ca ˘ dariu and Radu, we will discuss the stability of the solutions for this functional equation.